Answer:
Simplifying
x = -25
Step-by-step explanation:
Reorder the terms:
10x + -6(5 + 2x) = 20
10x + (5 * -6 + 2x * -6) = 20
10x + (-30 + -12x) = 20
Reorder the terms:
-30 + 10x + -12x = 20
Combine like terms: 10x + -12x = -2x
-30 + -2x = 20
Solving
-30 + -2x = 20
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '30' to each side of the equation.
-30 + 30 + -2x = 20 + 30
Combine like terms: -30 + 30 = 0
0 + -2x = 20 + 30
-2x = 20 + 30
Combine like terms: 20 + 30 = 50
-2x = 50
Divide each side by '-2'.
x = -25
5x = 25
x = 5
anything 2 ask please pm me
The formula for the standard error is this:
σM = σ / √N
where
σM is the standard error
σ is the standard deviation
N is the number of samples
So,
σM = 0.45 / √50
σM = 0.0636 or 6.36%
The standard error is 0.0636
Answer:
The median of the data set:
6, 15, 30, 45, 47, 49
The middle numbers are 30 and 45 so
You have to do 30 + 45
= 75
Then do 75 ÷ 2
= 37.5
The mean of the data set:
47, 15, 6, 49, 45, 30 (add them all)
= 192
Then divide 192 by 6 (because there are 6 numbers)
192 ÷ 6
= 32
So the median is 37.5 and the mean is 32.
Step-by-step explanation:
Hope this helps!
From your neighborhood softie :)
Answer:
y = 2*x^2 - 2*x - 24
Step-by-step explanation:
If we have a quadratic function with roots a and b, we can write the equation for that function as:
y = f(x) = A*(x - a)*(x - b)
Where A is the leading coefficient.
In this case, we know that the roots are: 4 and -3
Then the function will be something like:
f(x) = A*(x - 4)*(x - (-3) )
f(x) = A*(x - 4)*(x + 3)
Now we need to determine the value of A.
We also know that the graph of the function passes through the point (3, -12)
This means that:
f(3) = -12
Then:
-12 = A*(3 - 4)*(3 + 3)
-12 = A*(-1)*(6)
-12 = A*(-6)
-12/-6 = A
2 = A
Then the equation is:
y = f(x) = 2*(x - 4)*(x + 3)
Now we need to write this in standard form, so we just need to expand the equation:
y = f(x) = 2*(x^2 + x*3 - x*4 - 4*3)
y = f(x) = 2*(x^2 - x - 12)
y = f(x) = 2*x^2 - 2*x - 24
Then the relation is:
y = 2*x^2 - 2*x - 24